Contaminated Re-usable Thermometers Are a Potential Vector for Dissemination of Pathogens. (4th October 2017) - John, Amrita; Rai, Herleen; Alhmidi, Heba; Mana, Thriveen Sankar Chittoor; Cadnum, Jennifer; Donskey, Curtis J
Abstract: Background: Portable medical equipment that is shared among patients may become contaminated with healthcare-associated pathogens, and cleaning of these devices is often suboptimal. Limited data are available on the potential for contaminated equipment to serve as a vector for pathogen dissemination. However, previous studies have suggested that the handles of re-usable thermometers may transmit pathogens. Methods: We used a DNA marker generated from cauliflower mosaic virus to study the potential for dissemination of pathogens by re-usable thermometers which are attached to the portable vital signs equipment used on a long-term care facility (LTCF) ward. The DNA marker was inoculated onto 6 thermometer handles. During a 24-hour period, radio-frequency identification (RFID) technology was used to monitor movement of the equipment and fluorescent markers were used to assess whether the equipment was cleaned. Polymerase chain reaction was used to determine whether the DNA marker contaminated high-touch surfaces in patient rooms, other portable equipment on the ward, and common areas. Results: Portable vital signs equipment entered 14 LTCF resident rooms during a 24-hour period. The DNA marker was detected on high touch surfaces in 3 of the 14 (21%) rooms and on 4 other items of shared portable equipment, but not in common areas. There was no evidence that the portable equipment was cleaned based on absence of removal of the fluorescent marker. Conclusion: Our findings demonstrate the potential for contaminated shared portable equipment such as re-usable thermometers to serve as a vector for dissemination of pathogens in the LTCF setting. There is a need for effective strategies to disinfect shared portable equipment between patients. Disclosures: All authors: No reported disclosures.